CircTTC13 promotes sorafenib resistance in hepatocellular carcinoma through the inhibition of ferroptosis by targeting the miR-513a-5p/SLC7A11 axis - Ying Zhang; Ruiwei Yao; Mingyi Li; Chongkai Fang; Kunliang Feng; Xiuru Chen; Jinan Wang; Rui Luo; Hanqian Shi; Xinqiu Chen; Xilin Zhao; Hanlin Huang; et al. (Molecular Cancer)
Abstract The high mortality rate from hepatocellular carcinoma (HCC) is due primarily to challenges in early diagnosis and the development of drug resistance in advanced stages. Many first-line chemotherapeutic drugs induce ferroptosis, a form of programmed cell death dependent on ferrous iron-mediated oxidative stress, suggesting that drug resistance and ensuing tumor progression may in part stem from reduced ferroptosis. Since circular RNAs (circRNAs) have been shown to influence tumor development, we examined whether specific circRNAs may regulate drug-induced ferroptosis in HCC. Through circRNA sequencing, we identified a novel hsa_circ_0000195 (circTTC13) that is overexpressed in HCC tissues. This overexpression is linked to higher tumor grade, more advanced tumor stage, decreased ferroptosis, and poorer overall survival. Overexpression of CircTTC13 in HCC cell lines and explant tumors was associated with increased proliferation rates, enhanced metastatic capacity, and resistance to sorafenib, while also inhibiting ferroptosis. Conversely, circTTC13 silencing reduced malignant characteristics and promoted ferroptosis. In silico analysis, luciferase assays, and fluorescence in situ hybridization collectively demonstrated that circTTC13 directly targets and reduces miR-513a-5p expression, which in turn leads to the upregulation of the negative ferroptosis regulator SLC7A11. Moreover, the inhibition of SLC7A11 mirrored the effect of circTTC13 knockdown, whereas ferroptosis inhibition mimicked the effect of circTTC13 overexpression. Both circTTC13 and SLC7A11 were highly expressed in drug-resistant HCC cells, and circTTC13 silencing induced ferroptosis and reversed sorafenib resistance in explant tumors. These findings identify circTTC13 as a critical driver of HCC progression and resistance to drug-induced ferroptosis via upregulation of SLC7A11. The cicTTC13/miR-513a-5p/SLC7A11 axis represents a potential therapeutic target for HCC.